Method for activating alkaline oxygen furnace steel slag
By adding phosphate compounds to BOF steel slag minerals as activators, the use of BOF steel slag in the cement and concrete industries is solved, and the effect of high compressive strength, low porosity and effective control of heavy metal leaching is achieved.
Patent Information
- Application Number
- CN202380064403.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-23
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-15
AI Technical Summary
The use of BOF steel slag in the cement and concrete industries is limited, mainly due to low hydraulic activity caused by low amorphous content, high inert phase, volume instability caused by free CaO, and heavy metal contamination such as vanadium and chromium.
The performance of its reactive binder is improved, the resistance to carbonization is enhanced, and the leaching of heavy metals is controlled by adding phosphate compounds to the BOF steel slag minerals as activators, such as potassium dihydrogen phosphate, dipotassium hydrogen phosphate and tripotassium phosphate.
The effective activation of BOF steel slag minerals is achieved, the compressive strength of building materials is improved, the porosity is reduced, and the leaching of heavy metals is effectively controlled during carbonization, meeting the limit value of the Dutch soil quality law.
Smart Images

Figure CN119836407A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for activating basic oxygen furnace slag minerals, to a mixture containing activated BOF slag minerals, and to a building material or building product based on the activated BOF slag minerals. Background Art
[0002] Basic oxygen steelmaking (abbreviated BOS, BOP or BOF), also known as Linz-Donawitz steelmaking or converter oxygen steelmaking, is a primary steelmaking process that makes steel from carbon-rich molten pig iron. Blowing oxygen through lances above the molten pig iron in a converter reduces the carbon content of the alloy and converts it into a low-carbon steel. The process is called "basic" because a flux of chemically alkaline slaked lime or dolomite is added to facilitate the removal of impurities and protect the converter lining.
[0003] A byproduct of the basic oxygen steelmaking process is basic oxygen furnace (BOF) slag. For every ton of steel produced, about 80-110 kg of BOF slag is produced. Currently, a large amount of BOF slag is landfilled or temporarily stored, causing potential environmental problems. BOF slag is composed of: CaO 35-60 wt%, SiO2 10-15 wt%, total Fe content (expressed as FeO) 15-35 wt% (Fe2O3 3-10 wt% and FeO 15-25 wt%), Al2O3 1-5 wt%, MgO 3-13 wt% and P2O5 1-4 wt%. Its mineral composition is expressed by C2S, C3S, C2F, RO phase (CaO-FeO-MgO-MnO solid solution), magnetite and C4AF.
[0004] Blast furnace slag is different from BOF steel slag. Blast furnace slag is produced by smelting iron ore, coke and flux during the operation of extracting iron from iron ore, and BOF steel slag is formed during the refining operation of converting crude iron into steel by combining flux with non-iron oxides and other undesirable elements in the raw materials in a molten state. Blast furnace slag is composed of: CaO 34-42% by weight, SiO2 28-38% by weight, Al2O3 8-20% by weight, MgO 6-12% by weight, and a very low total Fe content of less than 2% by weight, the total Fe content being expressed as FeO (FeO, Fe2O3).
[0005] Patent document US-5,553,670 discloses a method and composition for cementing a well by mixing water, blast furnace slag and a compound containing phosphate ions to form a cement slurry, placing the cement slurry in a well, and allowing the cement slurry to solidify. Discloses the use of trisodium hexametaphosphate, trisodium tripolyphosphate and tetrasodium polyphosphate as activators to reduce the setting time of the cement slurry. In these examples, commercially available "NEWCEM" blast furnace slag is used in combination with 50% distilled water (based on the weight of the slag).
[0006] Patent document US-2011 / 0232532-A1 discloses a composition capable of solidifying to produce a building material, the composition comprising: 1-55% by weight of a pozzolan material, 1-30% by weight of an activator, 40-90% by weight of aggregate and a sufficient amount of liquid landfill leachate so that the composition solidifies into a building material with a compressive strength of at least 2.0 MPa. The pozzolan material (pozzolan) is selected from fly ash, silica fume, metakaolin, ground granulated blast furnace slag, and mixtures thereof. Preferably, the pozzolan material is fly ash. Preferably, the liquid landfill leachate is recovered from a landfill comprising at least one coal combustion product (CCP), the coal combustion product being selected from fly ash, bottom ash, boiler slag and flue gas desulfurization material.
[0007] However, the use of BOF slag in the cement and concrete industry is limited due to a number of technical barriers, namely low hydraulic activity due to low amorphous content, high amounts of inert phases, volume instability problems due to the presence of free CaO, and contamination with heavy metals, especially vanadium and chromium. Furthermore, even after application as a building material, carbonation resistance is always relevant, as carbonization can lead to leaching of heavy metal ions. Summary of the invention
[0008] The object of the present invention is to provide a method for activating BOF steel slag minerals.
[0009] The object of the present invention is to provide a BOF steel slag mineral to be used as a reactive binder in the field of cement and concrete technology.
[0010] Another object of the present invention is to enhance the carbonization resistance of BOF slag minerals, especially when used in BOF slag based building materials.
[0011] Another object of the present invention is to provide a BOF steel slag mineral that effectively controls leaching during carbonization.
[0012] These and other objects and further advantages are met or exceeded by the invention according to claim 1 and the preferred embodiments set out in the dependent claims.
[0013] To achieve these objectives, the present invention provides, in a first aspect, a method for activating basic oxygen furnace (BOF) slag minerals used in building products, the method comprising the step of adding an activator to the basic oxygen furnace (BOF) slag mineral, wherein the activator is a phosphate compound selected from the group consisting of potassium dihydrogen phosphate, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, dipotassium hydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate, tripotassium phosphate, trisodium phosphate, triammonium phosphate or a combination thereof.
[0014] Based on the above, one or more objects have been achieved. According to the present invention, it has been found that by adding a phosphate compound selected from potassium dihydrogen phosphate, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, dipotassium hydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate, tripotassium phosphate, trisodium phosphate, triammonium phosphate or a combination thereof, BOF steel slag powder is converted into a cement-free cementitious material, thereby meeting the requirements of strength development and environmental protection.
[0015] In one embodiment, the total amount of potassium dihydrogen phosphate, sodium dihydrogen phosphate and / or ammonium dihydrogen phosphate is up to 15 wt%, preferably up to 10 wt%, based on the amount of basic oxygen furnace (BOF) slag mineral.
[0016] In another embodiment, the total amount of dipotassium hydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate, tripotassium phosphate, trisodium phosphate and / or triammonium phosphate is up to 10 wt%, preferably up to 5 wt%, based on the amount of basic oxygen furnace (BOF) slag mineral.
[0017] In a preferred embodiment, the activator is a phosphate compound selected from the group consisting of potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate or a combination thereof. Experimental results have shown that these compounds, in particular at least each of potassium dihydrogen phosphate and dipotassium hydrogen phosphate, can provide approximately the same compressive strength level in building products or building materials, and each of dipotassium hydrogen phosphate and tripotassium phosphate requires a lower addition amount to achieve approximately the same result as potassium dihydrogen phosphate. It has been demonstrated that dipotassium hydrogen phosphate and tripotassium phosphate provide even better leaching results than potassium dihydrogen phosphate, at least for vanadium and chromium. All of these ingredients as activators provide leaching performance of vanadium and chromium within the limits of the Dutch Soil Quality Decree, 2007, "Regeling Bodemkwaliteit", Annex A, as part of Section 3.3. (i.e. SQD limit values: V<1.80mg / kg, and Cr<0.63mg / kg).
[0018] In one embodiment, the activator is potassium dihydrogen phosphate (KH2PO4). The total amount of the activator is up to 15 wt%, preferably up to 10 wt%, based on the amount of basic oxygen furnace (BOF) slag mineral. In one embodiment, at least 0.10 wt%, preferably at least 0.50 wt%, based on the amount of basic oxygen furnace (BOF) slag mineral, is present.
[0019] In one embodiment, the activator is dipotassium hydrogen phosphate (K2HPO4). The total amount of the activator is up to 10 wt%, preferably up to 5 wt%, more preferably up to 3.5 wt%, based on the amount of basic oxygen furnace (BOF) slag mineral. In one embodiment, at least 0.10 wt%, preferably at least 0.50 wt%, based on the amount of basic oxygen furnace (BOF) slag mineral, is present.
[0020] In one embodiment, the activator is tripotassium phosphate (K3PO4). The total amount of the activator is up to 10 wt%, preferably up to 5 wt%, more preferably up to 3.5 wt%, based on the amount of basic oxygen furnace (BOF) slag mineral. In one embodiment, at least 0.10 wt%, preferably at least 0.50 wt%, based on the amount of basic oxygen furnace (BOF) slag mineral, is present.
[0021] When potassium dihydrogen phosphate, dipotassium hydrogen phosphate and / or tripotassium phosphate are added in combination, for example dipotassium hydrogen phosphate together with tripotassium phosphate, the combined total amount of phosphate compounds is in the range of 0.10-10 wt %, preferably in the range of 0.10-5 wt %, more preferably in the range of 0.50-3.5 wt %, based on the amount of basic oxygen furnace (BOF) slag mineral, and has the preferred ranges as described and claimed herein.
[0022] As known to those skilled in the art, a combination of phosphoric acid and tripotassium phosphate may also be used in appropriate stoichiometric ratios to prepare a solution containing the activator potassium dihydrogen phosphate or dipotassium hydrogen phosphate or a combination thereof.
[0023] Each of potassium dihydrogen phosphate, dipotassium hydrogen phosphate and tripotassium phosphate is known in other non-metallurgical technical fields and is accepted as an additive or agent, for example, as a fertilizer, a food additive, an acidity regulator or an emulsifier.
[0024] In one embodiment, the method for activating Basic Oxygen Furnace (BOF) steel slag mineral further comprises the step of adding water to the mixture of the activator and the Basic Oxygen Furnace (BOF) steel slag mineral.
[0025] In one embodiment, the water to solid ratio is at most 0.25, preferably at most 0.22, more preferably at most 0.20, wherein solid refers to the amount of activator in the form of basic oxygen furnace (BOF) slag minerals and phosphate compounds. Therefore, if any other additives (such as sand) are added, these additives are not included in the water to solid ratio. Preferably, the activator is a phosphate selected from potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate or a combination thereof. In one embodiment, the water to solid ratio is at least 0.10, more preferably at least 0.12. When the water to solid ratio of the slag mixture is less than 0.10, the slag mixture will be too dry and therefore difficult to process. Therefore, the water to solid ratio is preferably at least 0.10 so that mixing and pouring of the paste can be achieved. Excess water can lead to increased porosity and reduced compressive strength of the building product. Therefore, the water to solid ratio is preferably at most 0.25. Furthermore, to avoid seepage and segregation, the water to solids ratio should preferably be below 0.25.
[0026] In one embodiment of the method for activating Basic Oxygen Furnace (BOF) slag mineral, further comprising the step of mixing water with an activator in the form of a phosphate compound, and a subsequent step of adding the mixture so obtained to the Basic Oxygen Furnace (BOF) slag mineral. In one embodiment, the ratio of water to solids is at most 0.25, preferably at most 0.22, more preferably at most 0.20, wherein solids refer to the amount of Basic Oxygen Furnace (BOF) slag mineral and the activator in the form of a phosphate compound. In one embodiment, the ratio of water to solids is at least 0.10.
[0027] In one embodiment according to the present invention, the BOF slag mineral particle size is at most 500 microns, preferably at most 150 microns. The BOF slag particle size is preferably at most 500 microns to increase the exposure of the hydrating phase to the activator, thereby reducing the reaction time and improving the uniformity of the product. This BOF slag particle size can be obtained by several methods known to those skilled in the art.
[0028] In one embodiment of the present invention, the basic oxygen furnace (BOF) slag mineral is ground so that the median particle size of the basic oxygen furnace (BOF) slag mineral is at most 25 microns, preferably at most 20 microns, more preferably at most 15 microns. The median particle size is preferably at most 25 microns to increase the exposure of the hydrating phase to the activator, to reduce the reaction time and to improve the uniformity of the product.
[0029] In one embodiment of the present invention, the basic oxygen furnace (BOF) steel slag mineral is ground so that the D50 average grain size of the basic oxygen furnace (BOF) steel slag mineral is at most 25 microns, preferably at most 20 microns, and more preferably at most 17 microns. The term "D50" refers to the mean or average particle diameter, which is considered to be the average particle size by mass. A D50 of 25 microns means that the average particle diameter is 25 microns; it also means that 50% of the sample mass consists of particles less than 25 microns, and 50% is larger. The D50 does not exceed a maximum of 25 microns to increase the exposure of the hydrating phase to the activator, to reduce the reaction time and to improve the uniformity of the product. The inventors have found that although lower D50 values are desirable, excellent results can be obtained when the D50 has a lower limit of at most 10 microns. In one embodiment, the D90 average particle size is at most 35 microns, preferably at most 30 microns.
[0030] The particle size distribution of BOF slag minerals can be measured, for example, by laser diffraction techniques (eg Mastersizer 2000, Malvern).
[0031] In one embodiment according to the present invention, the BOF slag comprises 10-30 wt% of brownmillerite, 0-15 wt% of magnetite, 25-60 wt% of C2S, 10-30 wt% of Mg-wuestite, 0-20 wt% of C3S and 0-6 wt% of free CaO. C2S or belittonite and brownmillerite are usually present in converter slag. Analysis of the solid phase of the slag paste shows that the addition of potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate or a combination thereof promotes the dissolution and hydration of C2F and C2S, thereby contributing to the development of compressive strength of the resulting building product.
[0032] In an embodiment according to the present invention, the BOF steel slag contains 35-60 wt% CaO, 10-17 wt% SiO2, 15-35 wt% ΣFe oxide, 1-5 wt% Al2O3, 1-13 wt% MgO, 0-4 wt% P2O5, 0-2 wt% TiO2, and the remainder of impurities.
[0033] In one aspect of the invention, it relates to a slag mixture or paste comprising a BOF slag mineral, an activator in the form of a phosphate compound as described and claimed herein, and a combination of water alone. The slag mixture can be used to prepare a building product or building material with excellent compressive strength. In one embodiment, the seven-day compressive strength and / or twenty-eight-day compressive strength of the building product or building material are at least 20.0 MPa and 35.0 MPa, respectively. In one embodiment, the twenty-eight-day compressive strength of the building product or building material is at least 40 MPa. In these embodiments, the slag mixture typically has a water-to-solid ratio of up to 0.25. Alternatively, the slag mixture may contain other additives such as sand, gravel and / or limestone, resulting in a mortar or concrete-like mixture. This allows for a wider application of BOF slag minerals in high-end building products, which may significantly reduce landfilled BOF slag.
[0034] In another aspect of the present invention, there is provided a method for preparing a building product, the method comprising the steps of:
[0035] a) Provide Basic Oxygen Furnace (BOF) slag minerals; and
[0036] b) optionally providing solid additives such as sand, gravel and / or limestone;
[0037] c) adding an aqueous solution of an activator comprising a phosphate compound as described and claimed herein;
[0038] d) mixing the ingredients of steps a) to c) to obtain a steel slag mixture paste meeting the above specifications;
[0039] e) applying the slag mixture or slag paste into the mold;
[0040] f) solidifying the slag mixture or slag paste to obtain a building product.
[0041] The method according to the invention can be used per se for producing high-strength prefabricated building elements or building products under ambient conditions. The BOF slag mineral is activated with an activator in the form of a phosphate compound, thereby obtaining high performance of the resulting building product, such as high compressive strength, low porosity and very limited heavy metal leaching (if any). The solid components can be added in any order and mixed with an aqueous solution of an activator comprising a phosphate compound. The slag mixture consisting of the BOF slag mineral, the activator in the form of a phosphate compound and water alone is generally referred to as a paste. The slag mixture consisting of a combination of the BOF slag mineral, the activator in the form of a phosphate compound, water and sand (usually about 2 / 3 of the mass is sand) is generally referred to as a mortar. By mixing, a uniform slag mixture is obtained, which can be added to a mold. The method can be carried out under ambient conditions without the need for special curing conditions. The adequate workability of the mixture is reflected in the uniform distribution of the phases in the hydrated mixture, the adequate spreading flow of the mixture and the low porosity of the final formed building product.
[0042] Alternatively, there is provided a method of preparing a building product, the method comprising the steps of:
[0043] a) Provide basic oxygen furnace (BOF) slag minerals;
[0044] b) optionally providing solid additives such as sand, gravel and / or limestone;
[0045] c) providing an activator comprising a phosphate compound as described and claimed herein and mixing the ingredients of steps a) to c);
[0046] d) adding water;
[0047] e) mixing the ingredients of steps a)-d) to obtain a slag mixture (paste or mortar) meeting the above specifications;
[0048] f) applying the slag mixture into the mold;
[0049] g) solidifying the slag mixture to obtain a building product.
[0050] These methods can be used to produce high-strength prefabricated building components under ambient conditions. The BOF steel slag mineral is activated with an activator in the form of a phosphate compound, thereby obtaining high performance of the resulting product (e.g. high compressive strength, low porosity). The solid ingredients can be added in any order, optionally premixed, and mixed with water. By mixing, a homogeneous slag mixture is obtained, which can be transferred to a mold. The method can be carried out under ambient conditions without the need for special curing conditions. The adequate workability of the mixture is reflected in the uniform distribution of the phases in the hydrated mixture, the adequate spreading flow of the mixture and the low porosity of the final formed building product.
[0051] For both methods, the slag mixture is preferably solidified in the mold within a desired setting time, wherein the setting time ranges from 1 to 72 hours. The setting time is related to the amount of activator and water added. The setting time is preferably at least about 1 hour to allow workers to mold the slag mixture into their desired shape. The setting time is preferably at most about 24 hours. After solidification, the building product can be demoulded, thereby reducing the time in the mold. The curing typically continues after demoulding, and the mold can be used for the next building product.
[0052] The present invention is suitable for converting BOF slag minerals that are currently landfilled or used at a low level into high-end molded building products with high compressive strength. In addition, in Europe, the annual production of BOF slag exceeds 10 million tons. Building materials based on BOF slag can be produced directly in concrete manufacturing companies without special investment. Since BOF slag is currently landfilled, the production cost is limited to the price of activators and water in the form of phosphate compounds described and claimed herein. Compared with standard paste or concrete manufacturing, no additional equipment is required. The seven-day compressive strength and / or twenty-eight-day compressive strength of the resulting building product are at least 20.0 MPa and 35.0 MPa, respectively, and are measured according to EN 196-1 (repeated three times for each composition). In one embodiment, the twenty-eight-day compressive strength of the building product or building material is at least about 40 MPa.
[0053] In one embodiment according to the present invention, the building product has a mesoporous structure. The average pore size is preferably in the range of 2-50 nm, more preferably in the range of 2-20 nm. The mesoporous structure has the advantages of being able to obtain higher uniformity and higher compressive strength as well as high durability.
[0054] In one embodiment according to the invention, the leaching performance of the building product before and after carbonization, most particularly for vanadium and chromium, is within the limits of the Dutch Soil Quality Decree (Dutch Soil Quality Decree, 2007, "Regeling Bodemkwaliteit", Annex A, as part of Section 3.3). (i.e. SQD limit values: V < 1.80 mg / kg, and Cr < 0.63 mg / kg).
[0055] The leaching can be measured according to EN 12457-2 (one-stage batch leaching test).
[0056] The cementing phases (clinostomite and linderite) are also the most polluted phases in steel slag, which means the risk of heavy metal leaching during the hydration and service life of steel slag pastes and mortars. Since heavy metals derived from linderite (mainly chromium and vanadium) and clinostomite (mainly vanadium) are also present in the hydration products, the steel slag mixture according to the invention leads to the immobilization of heavy metals, thereby significantly reducing the leaching of heavy metals.
[0057] In another aspect of the present invention, it relates to a premix kit, i.e. in dry form, for obtaining a building product comprising BOF slag and an activator in the form of a phosphate compound, wherein the phosphate compound ranges from 0.10 to 15 wt.%, preferably 0.10 to 10 wt.%, more preferably 0.10 to 5 wt.% of the BOF slag mineral. The BOF slag mineral and the phosphate compound activator are as described and claimed herein. The premix kit can be used to prepare high-end formed building products instantly by adding water, mixing and curing as known in the art.
[0058] In another aspect of the present invention, it relates to the use of a phosphate compound selected from potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate or a combination thereof as an activator for BOF slag minerals in the production of formed building products and reducing the leaching of at least vanadium and chromium to within the limits of the Dutch Soil Quality Decree, 2007, "Regeling Bodemkwaliteit", Annex A, as part of Section 3.3. (i.e. SQD limit values: V < 1.80 mg / kg, and Cr < 0.63 mg / kg). The total amount of potassium dihydrogen phosphate is in the range of 0.10-15 wt. % based on the amount of basic oxygen furnace (BOF) slag minerals, and the preferred ranges are as described and claimed herein. The total amount of dipotassium hydrogen phosphate is in the range of 0.10-10 wt %, and preferably in the range of 0.10-5 wt %, based on the amount of basic oxygen furnace (BOF) slag mineral, with preferred ranges as described and claimed herein. The total amount of tripotassium phosphate is in the range of 0.10-10 wt %, and preferably in the range of 0.10-5 wt %, based on the amount of basic oxygen furnace (BOF) slag mineral, with preferred ranges as described and claimed herein. When potassium dihydrogen phosphate, dipotassium hydrogen phosphate and / or tripotassium phosphate are added in combination, for example, dipotassium hydrogen phosphate together with tripotassium phosphate, the total amount of phosphate compounds is in the range of 0.10-10 wt %, and preferably in the range of 0.10-5 wt %, and more preferably 0.50-3.5 wt %, based on the amount of basic oxygen furnace (BOF) slag mineral, with preferred ranges as described and claimed herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The invention will now be illustrated by the following non-limiting figures and embodiments according to the invention.
[0060] FIG. 1 shows (a) the particle size distribution of the used BOF slag, and (b) the cumulative particle size distribution.
[0061] Figure 2 is the compressive strength of BOF slag paste with KH2PO4 dosage ranging from 0 to 10 wt% after 7 and 28 days of curing.
[0062] FIG. 3 shows (a) the cumulative heat release of BOF steel slag paste and (b) the heat flow of BOF steel slag paste, wherein the amount of potassium dihydrogen phosphate (MKP) is varied from 0 to 10 wt %.
[0063] Figure 4 are XRD data of hydrated samples with potassium dihydrogen phosphate (MKP) dosage (Legend: B-melferite, L-calcite, M-magnetite, W-wüstite, H-hydrogarnet, Ht-hydrotalcite).
[0064] Figure 5 is the FTIR spectrum of BOF slag paste after 28 days of hydration.
[0065] 6 is a thermal analysis (DTG) of BOF slag paste with potassium dihydrogen phosphate (MKP) dosage varied from 0 to 10 wt % after 7 and 28 days of hydration.
[0066] Figure 7 Representative BSE images and phase distribution diagrams of 28-day hydrated BOF slag paste with 5 wt% MKP dosage.
[0067] Figure 8 It is the compressive strength of BOF slag paste with dipotassium hydrogen phosphate (DKP) dosage ranging from 0 to 3 wt% after curing for 7 and 28 days.
[0068] Fig. 9 The XRD data of the hydrated sample with 2 wt% dipotassium hydrogen phosphate (DKP) (illustration: H-hydrogarnet, Ht-hydrotalcite).
[0069] 10 is a thermal analysis (DTG) of BOF slag paste with dipotassium phosphate (DKP) dosage varied from 0 to 3 wt % after 7 and 28 days of hydration.
[0070] 11 is a thermal analysis (DTG) of 28-day hydrated BOF slag paste with dipotassium phosphate (DKP) dosage varied from 0 to 3 wt % after 3 and 14 days of carbonization.
[0071] Fig.12 The compressive strength of BOF slag pastes with monopotassium phosphate (MKP), dipotassium phosphate (DKP), tripotassium phosphate (DKP) and their combination after 7 and 28 days of curing.
[0072] Table 1 relates to the mineralogical and chemical composition of typical BOF slags used in these studies.
[0073] Table 2 relates to the average chemical compositions of the main phases in 28-day hydrated BOF slag.
[0074] Table 3 relates to the leaching of inorganic contaminants measured by a one-stage batch leaching test and the SQD limit values stipulated in the Dutch Soil Quality Ordinance.
[0075] Table 4 relates to the leaching of inorganic contaminants measured by a one-stage batch leaching test on a 28-day cured BOF slag paste, and the SQD limit values specified in the Dutch Soil Quality Ordinance.
[0076] Table 5 relates to the leaching of inorganic contaminants measured by a one-stage batch leaching test of a 14-day carbonized BOF slag paste, and the SQD limit values specified in the Dutch Soil Quality Ordinance.
[0077] Table 6 relates to the porosity of dipotassium phosphate (DKP) activated BOF slag before and after carbonization, relative to non-activated BOF slag.
[0078] Table 7 relates to the phase composition of dipotassium phosphate (DKP) activated BOF slag after 28 days of hydration.
[0079] Table 8 relates to the amounts of MKP, DKP, TKP and some combinations used for compressive strength testing after 7 and 28 days of curing. DETAILED DESCRIPTION
[0080] BOF slag contains a large amount of C2S and C2F and X-ray amorphous, which in this example accounts for about 65-70% by weight of the total amount of mineral compounds (as shown in Table 1), which are the target phases to be activated. The BOF slag was ground using a disc mill for 15 minutes to obtain a median particle size of about 17 microns, as shown in Figure 1, to expose the hydrated phase. First, potassium dihydrogen phosphate (MKP) was selected as an activator, which can also be used as a fertilizer, food additive or buffer in other technical fields. The maximum addition amount of potassium dihydrogen phosphate is 15% by weight of the mass of BOF slag, and the preferred maximum amount is 10% by weight. Potassium dihydrogen phosphate is directly mixed with the BOF slag powder to obtain a uniform distribution, and then water is added at a water-to-solid ratio of 0.2. The operation is carried out under ambient conditions and no special curing conditions are required. The prepared samples obtained 7-day compressive strength and 28-day compressive strength (up to 19.8 MPa and 44.5 MPa, respectively. Figure 2 ). The setting time varies from 3 minutes to 24 hours or even longer, depending on the amount of KH2PO4 added. The addition of KH2PO4 promotes the dissolution and hydration of C2F and C2S compared to the reference sample, which then improves the mechanical properties, consistent with the high exotherm shown in Figure 3. Figure 4 and Figure 5 As shown in Figure 6, the main hydration products are hydrotalcite, hydrogarnet, CSH gel and hydroxyapatite-like minerals, which is further confirmed by thermogravimetric analysis (Figure 6). At the same time, the leaching of BOF slag paste after 28 days of hydration meets the regulatory requirements (Table 3), which can be explained by the incorporation of heavy metals in the hydration products (Table 2).
[0081] Dipotassium hydrogen phosphate (DKP) with high water solubility can replace potassium dihydrogen phosphate (MKP), which can also be used as a fertilizer, food additive or buffer in other technical fields. The maximum addition amount of dipotassium hydrogen phosphate is 10% by weight of the mass of BOF slag, and the preferred maximum amount is 5% by weight. In this embodiment, the ratio of water to solid (BOF slag + DKP) is 0.18. Before mixing, dipotassium hydrogen phosphate is first added to the water to ensure uniform dispersion. The operation is carried out under ambient conditions and no special curing conditions are required. The prepared specimens obtained 7-day compressive strength and 28-day compressive strength of up to 26.7 MPa and 42.5 MPa, respectively (see Figure 8 ). Similar to potassium dihydrogen phosphate, the addition of dipotassium hydrogen phosphate promotes the formation of hydrotalcite, hydrogarnet, CSH gel and hydroxyapatite-like minerals, such as Fig. 9 and Figure 10. The high carbonization resistance of the dipotassium hydrogen phosphate activated BOF slag was demonstrated by thermogravimetric analysis, which showed minor changes after 14 days of carbonization compared to the reference sample. In addition, the leaching behavior of the 28-day hydrated BOF slag paste before and after 14 days of carbonization met regulatory requirements (Tables 4 and 5).
[0082] The method of the present invention for activating Basic Oxygen Furnace (BOF) slag minerals can be used to produce high strength prefabricated building components having high resistance to carbonization under ambient conditions.
[0083] For Table 1, the elemental composition was determined by XRF (molten bead method). The mineralogical composition of the BOF slag was analyzed by X-ray diffraction (D2 PHASER X-ray diffractometer equipped with a Co X-ray tube) using the corundum external standard method. The samples were scanned on a rotating stage (autorotation speed of 10 rpm) using a step size of 0.02° and a time of 2 seconds per step for a 2θ range of 7-90°. Quantitative Rietveld refinement was performed using TOPAS Academic software v5.0.
[0084] For Table 2, the oxide compositions of the phases in the hydrated BOF slag are from the PARC results (PhAse Recognition and Characterization) described in the following literature: C. van Hoek et al., "Large-Area Phase Mapping Using PhAse Recognition and Characterization (PARC) Software", Microscopy-Today, September 2016, pp. 12-20.
[0085] For Table 3, batch leaching tests were performed on 28-day cured steel slag pastes according to EN 12457-2 (one-stage batch leaching test). The element concentrations obtained were compared with the limit values specified in the Dutch Soil Quality Ordinance.
[0086] For Table 4, batch leaching tests were performed on 28-day cured steel slag pastes according to EN 12457-2 (one-stage batch leaching test). The element concentrations obtained were compared with the limit values specified in the Dutch Soil Quality Ordinance.
[0087] For Table 5, a batch leaching test (one-stage batch leaching test) was performed on a 14-day carbonized BOF slag paste according to EN 12457-2. The element concentrations obtained were compared with the limit values specified in the Dutch Soil Quality Ordinance.
[0088] For Table 7, the elemental composition was determined using a D4ENDEAVOR X-ray diffractometer equipped with a LynxEye detector and a Co X-ray tube (operated at 40 KV and 40 mA). Diffraction measurements were performed using a step size of 0.019° and a counting time of 1 second per step. A variable divergence slit (V20) was used, and the scan range covered 2θ from 10 to 90°.
[0089] For Figure 1, BOF slag was ground in a disc mill (Retsch, RS300XL). The particle size distribution of the mechanically treated BOF slag was measured by laser diffraction technology (Mastersizer 2000, Malvern). For Figure 1(b), D50 was 17 microns and D90 was 107 microns.
[0090] For Figure 3, an isothermal conductivity calorimeter (TAM Air, Thermometric) was used. In order to evaluate the cumulative heat, the heat flow curves were integrated between 45 minutes and 23 days. In particular, MKP2.5 was tested up to 32 days because it experienced a rather long induction period.
[0091] for Figure 5 , located at 1034cm -1 、604cm -1 and 502cm -1 The bands at are associated with phosphate groups in apatite-like minerals.
[0092] As for Figure 11, the slight change of the calcite peak in the KHPO4 activated BOF slag compared to the reference BOF slag shows the excellent carbonization resistance.
[0093] Example
[0094] Based on the results from preliminary experiments, a reference sample compared to KH2PO4 activated BOF slag was prepared using a mixer at a water to solid ratio of 0.2 and a water to solid ratio of 0.18 for the reference sample compared to KH2PO4 activated BOF slag. The BOF slag powder was first mixed with water at a low speed for 30 seconds, then manually homogenized for another 30 seconds, and then mixed at a high speed for another 60 seconds.
[0095] First, potassium dihydrogen phosphate was mixed with BOF slag powder at a low speed for 30 seconds in a mixer to obtain a uniform distribution, and the amount of potassium dihydrogen phosphate was equivalent to 2.5, 5, and 10% by weight of BOF slag. Then water was added to the dry mixture at a water-to-solid ratio of 0.2 (BOF slag plus potassium dihydrogen phosphate). Mixed at a low speed for 30 seconds, then manually homogenized for another 30 seconds, and then mixed at a high speed for 60 seconds to obtain a BOF slag paste activated by potassium dihydrogen phosphate. The fresh BOF slag paste was poured into a foam mold (40×40×160mm) and then covered with a plastic film before demoulding. Due to different setting times, samples of 5% by weight and 10% by weight can be demoulded after 24 hours, while samples of 0% by weight and 2.5% by weight need to be carefully demoulded after 7 days to ensure sufficient hardening. Thereafter, the paste was demoulded, covered with foil, and cured in air at ambient temperature until the test period. The 7-day compressive strength and the 28-day compressive strength were determined according to EN 196-1 in triplicate for each composition.
[0096] The samples described here are based on the addition amount of potassium dihydrogen phosphate, and the amounts of potassium dihydrogen phosphate for 0, 2.5, 5, and 10 weight % are MKP0, MKP2.5, MKP5, and MKP10, respectively.
[0097] Before mixing, dipotassium hydrogen phosphate was first added to the water to ensure uniform dispersion, the amount of dipotassium hydrogen phosphate corresponding to 1, 2 and 3% by weight of BOF slag. The ratio of water to solid (BOF slag + DKP) was 0.18. The BOF slag powder was first mixed with the dipotassium hydrogen phosphate solution at low speed for 30 seconds, then manually homogenized for another 30 seconds, and then mixed at high speed for 60 seconds to obtain a dipotassium hydrogen phosphate activated BOF slag paste. The fresh BOF slag paste was poured into a foam mold (40×40×160 mm) and then covered with a plastic film before demoulding after 3 days to ensure sufficient hardening. Thereafter, the paste was demoulded, covered with foil, and cured in air at ambient temperature until the test period. The 7-day compressive strength and 28-day compressive strength were determined according to EN 196-1, repeated three times for each composition.
[0098] The samples described here are based on the addition of dipotassium hydrogen phosphate, and the DKP dosages of 0, 1, 2, and 3 wt% are DKP0, DKP1, DKP2, and DKP3 respectively.
[0099] The samples of BOF steel slag activated with dipotassium hydrogen phosphate and the corresponding reference BOF steel slag were selected for carbonization resistance test. After curing for 28 days, the samples were placed in a CO2 chamber with a CO2 concentration of 20% and a relative humidity of 80% for 3 days and 14 days. The designation of the carbonized samples is based on the carbonization period. For example, CDKP0-3d is a sample with 0 wt% DKP and after 3 days of carbonization.
[0100] After the designed curing period, the samples were manually broken to pass through a 4 mm sieve and then immersed in isopropanol for 24 hours to eliminate hydration and then dried in an oven at 45°C until constant weight. All dried samples were finely ground to pass through a 68 μm sieve and then stored in a desiccator with a desiccant (CaCl2 pellets) and sodium hydroxide pellets as a CO2 capture agent until further testing.
[0101] As can be seen from the results in Tables 4 and 5, significantly improved carbonization resistance and controllable heavy metal (particularly vanadium and chromium) leaching behavior before and after carbonization have been found.
[0102] From the results in Table 6, it can be seen that DKP2 causes a decrease in porosity in the DKP2 sample after carbonization (CDKP2). The addition of DKP also results in significantly lower porosity before and after carbonization compared to the sample without the addition of dipotassium hydrogen phosphate (DKP0).
[0103] From the results in Table 7, it can be seen that the addition of phosphate compounds, in this case dipotassium hydrogen phosphate (DKP), at increasing levels according to the present invention promotes the dissolution and hydration of C2F and C2S. As the amount of DPK present increases, the amount of C2F and C2S decreases after 28 days of hydration, and the amount of amorphous increases. Similar trends were found for monopotassium hydrogen phosphate (MKP) and tripotassium phosphate (TKP).
[0104] In a similar setup as above, other series of samples without phosphate compound (REF) or with defined amounts of monopotassium phosphate (MKP), dipotassium phosphate (DKP), tripotassium phosphate (TKP), MKP+DKP mixtures, and DKP+TKP mixtures were measured for compressive strength. The amount of phosphate compound added is listed in Table 8. For samples containing MKP, DKP, TKP, or a combination thereof, the water to solid ratio was 0.18, and for REF samples, the water to solid ratio was 0.2. The results are shown in Table 8. Fig.12 The compressive strength at 7 and 28 days was again determined according to EN 196-1 with three replicates for each composition.
[0105] Based on the above results and discussion, it has been found that BOF steel slag can be activated with a small amount of a specific group of phosphate compounds, preferably selected from the group consisting of: monopotassium phosphate, dipotassium hydrogen phosphate, tripotassium phosphate or a combination thereof. Figure 2 and Figure 8 The results show that potassium dihydrogen phosphate and dipotassium hydrogen phosphate can provide approximately the same compressive strength level, and the amount of dipotassium hydrogen phosphate required to achieve approximately the same result is lower. For tripotassium phosphate, similar or better results were found ( Fig.12 ). The combination of dipotassium hydrogen phosphate and tripotassium phosphate produced the highest compressive strength level. From the results in Tables 3-5, it can be seen that dipotassium hydrogen phosphate provides even better leaching results (at least for vanadium and chromium) than monopotassium phosphate. Similar results were found for tripotassium phosphate.
[0106] The product obtained according to the method of the present invention provides sufficient strength for use as a building material by adding a specific group of phosphate compounds, most preferably, the phosphate compound is selected from potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate or a combination thereof.
[0107] The inventors also found that the carbonization resistance was significantly improved and the leaching behavior of heavy metals (especially vanadium and chromium) before and after carbonization was controllable.
[0108] The above discussion is intended only to illustrate the present method and should not be construed as limiting the appended claims to any particular embodiment or group of embodiments. Therefore, the description and drawings should be regarded as illustrative and not intended to limit the scope of the appended claims. By studying the drawings, the disclosure and the appended claims, a person skilled in the art will be able to understand and implement other variations of the disclosed embodiments when practicing the claimed invention. The fact that certain measures are cited in different dependent claims does not indicate that a combination of these measures cannot be used to advantage.
[0109] Table 1. Mineralogy and chemical composition of BOF slag
[0110]
[0111]
[0112] Table 3. Leaching and SQD limits of inorganic contaminants measured by one-stage batch leaching tests
[0113]
[0114] Table 4. Leaching and SQD limits of inorganic contaminants measured by one-stage batch leaching tests
[0115]
[0116] Table 5. Leaching and SQD limits of inorganic contaminants measured by one-stage batch leaching tests
[0117]
[0118] Table 6. Porosity of DKP activated BOF slag before and after carbonization
[0119]
[0120]
[0121] Table 8. Sample mixing ratios of zero, MKP, DKP, TKP and mixtures (wt%)
[0122]
Claims
1. A method for activating basic oxygen furnace (BOF) steel slag mineral, comprising the step of adding an activator to the basic oxygen furnace (BOF) steel slag mineral, wherein the activator is a phosphate compound selected from the group consisting of: monopotassium phosphate, monosodium phosphate, monoammonium phosphate, dipotassium hydrogen phosphate, disodium hydrogen phosphate, diammonium hydrogen phosphate, tripotassium phosphate, trisodium phosphate, triammonium phosphate, or a combination thereof.
2. The method according to claim 1, wherein the activator is a phosphate compound selected from potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate or a combination thereof.
3. The method according to claim 1 or 2, wherein the activator is potassium dihydrogen phosphate in the range of up to 15 wt. %, preferably in the range of 0.10 to 15 wt. %, more preferably 0.10 to 10 wt. %, based on the amount of basic oxygen furnace (BOF) slag mineral.
4. The method according to claim 1 or 2, wherein the activator is dipotassium hydrogen phosphate in the range of up to 10 wt. %, preferably in the range of 0.10 to 10 wt. %, more preferably 0.10 to 5 wt. %, based on the amount of basic oxygen furnace (BOF) slag mineral.
5. The method according to claim 1 or 2, wherein the activator is tripotassium phosphate in the range of up to 10 wt. %, preferably in the range of 0.10 to 10 wt. %, more preferably 0.10 to 5 wt. %, based on the amount of basic oxygen furnace (BOF) slag mineral.
6. The method according to any one of claims 1 to 5, wherein the Basic Oxygen Furnace (BOF) slag mineral is ground such that the median particle size of the Basic Oxygen Furnace (BOF) slag mineral is at most 25 microns, preferably at most 20 microns.
7. The method according to any one of claims 1 to 6, wherein the basic oxygen furnace (BOF) slag mineral comprises: 10-30 wt% of linderite, 0-15 wt% of magnetite, 25-60 wt% of CS, 10-30 wt% of Mg-wüstite, 0-20 wt% of CS and 0-6 wt% of free CaO.
8. The method according to any one of claims 1 to 7, wherein the basic oxygen furnace (BOF) slag mineral comprises: 35-60 wt% CaO, 10-17 wt% SiO2, 15-35 wt% ΣFe oxide, 1-5 wt% Al2O3, 1-13 wt% MgO, 0-4 wt% P2O5, 0-2 wt% TiO2.
9. The method according to any one of claims 1 to 8, further comprising the step of adding water to the mixture of the activator and the Basic Oxygen Furnace (BOF) slag mineral to obtain a slag mixture.
10. The method according to claim 9, wherein the water to solids ratio is at most 0.25, preferably at most 0.22, and preferably at least 0.10, wherein solids refer to the amount of Basic Oxygen Furnace (BOF) slag minerals.
11. The method according to any one of claims 1 to 10, comprising the step of further adding one or more solid additives selected from sand, gravel and limestone.
12. The method according to any one of claims 9 to 11, further comprising the following steps: - mixing a basic oxygen furnace (BOF) slag mineral, an activator, water and optional solid additives to obtain a slag mixture; - applying the slag mixture into the mould; - Solidifying the slag mixture to obtain a building product.
13. A building product obtained by the method of claim 12, having a 7-day compressive strength of at least 20.0 MPa.
14. A building product according to claim 13 having a 28 day compressive strength of at least 35.0 MPa, preferably at least 40 MPa.
15. A building product according to claim 13 or 14, wherein the leaching performance for vanadium and chromium is within the limits of the Dutch Soil Quality Ordinance.
16. The building product according to any one of claims 13 to 15, wherein after subsequent carbonization the leaching performance for vanadium and chromium is within the limits of the Netherlands Soil Quality Ordinance.
17. A premix kit for obtaining a building product comprising a BOF steel slag mineral and an activator in the form of a phosphate compound selected from the group consisting of potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate or a combination thereof, and wherein the phosphate compound is 0.10 to 15 wt %, preferably 0.10 to 10 wt %, and more preferably 0.10 to 5 wt % of the BOF steel slag mineral.
18. Use of a phosphate compound selected from potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate or a combination thereof as an activator for BOF slag minerals in the production of building products to reduce the leaching of at least vanadium and chromium to within the limits of the Netherlands Soil Quality Ordinance, wherein the total amount of potassium dihydrogen phosphate is in the range of 0.10 to 15 wt.-%, based on the amount of Basic Oxygen Furnace (BOF) slag mineral, and the total amount of dipotassium hydrogen phosphate is in the range of 0.10 to 10 wt.-%, preferably 0.10 to 5 wt.-%, based on the amount of Basic Oxygen Furnace (BOF) slag mineral, and the total amount of tripotassium phosphate is in the range of 0.10 to 10 wt.-%, preferably 0.1 to 5 wt.-%, based on the amount of Basic Oxygen Furnace (BOF) slag mineral.
Citation Information
Patent Citations
Settable Building Material Composition Including Landfill Leachate
US20110232532A1
Optimizing blast furnace slag cements
US5553670A